Electrochemical genosensors as a new approach on plant DNA detection and quantification for honey authentication - Morais, Stephanie (2024)
Honey is a natural sweet food product with multiple nutritional and medicinal properties making it a healthy alternative to processed sugars. With the consumers’ recent interest and pur-chase of dietary products the global honey market has greatly increased. To keep up with produc-tion, or simply for financial gain, some producers/companies are now blending pure honey with cheaper substances that possess similar physical characteristics. As there are no notable visible dif-ferences between the pure and adulterated honey, it is extremely difficult to determine the purity of the available honeys. In this study, an electrochemical genosensor based on the sandwich format DNA hybridization reaction between two complementary probes was developed for the detection and quantification of Erica arborea pollen DNA in real samples. Analyzing public database platforms, a 98 base-pair DNA-target probe capable of unequivocally detecting the pollen from E. arborea was selected and designed. The complementary probe to the DNA-target oligonucleotide sequence was then cut into a 28 base-pair thiolated DNA-capture probe and a 70 base-pair fluorescein isothiocya-nate-labelled DNA-signaling probe. To increase the hybridization reaction, a self-assembled mono-layer formed from mixing the DNA-capture probe with mercaptohexanol was employed. Using chronoamperometry, the enzymatic amplification of the electrochemical signal was achieved with a concentration range of 0.03 to 2.00 nM. The DNA from certified E. arborea leaves was extracted using liquid nitrogen and mechanical grinding and the targeted region amplified by PCR. The de-veloped genosensor was successfully applied for the detection and quantification of the DNA con-centration of the extracted E. arborea plant leaves. So, the developed genosensor is a promising cost-effective and innovative analytical method to detect and quantify the DNA concentration of plant DNA in real honey samples.